Effects of Peer Education and Orientation Tour on Anxiety in Patient Candidates for Coronary Angiography - Farsi; Sajadi; Eslami (Kashan University of Medical Sciences, 2016)
Background Coronary angiography is a stressful procedure for most patients. The physiological responses caused by anxiety during coronary angiography increase the likelihood of dysrhythmia, coronary artery spasm, and rupture. Objectives This study compared the effects of peer education and an orientation tour on anxiety in patients who were candidates for coronary artery angiography. Patients and Methods This single blind quasi-experimental study was conducted in 2014. A total of 177 patients who were candidates for coronary artery angiography were divided into three groups: a peer education group, an orientation tour group, and a control group. The patients in the peer education group were trained by a peer educator, and the patients in in the orientation tour group were trained by the researcher, who worked in the angiography unit. The DASS-21 questionnaire was used to measure the patients' anxiety levels before the intervention and two hours before undergoing the coronary angiography. The data were analyzed using a Chi-square test, analysis of variance, the Kruskal-Wallis, Wilcoxon, Mann-Whitney U tests, and an interquartile range. Results The three groups did not significantly differ regarding the mean anxiety scores before the intervention. However, a significant difference was observed between the mean anxiety scores of the three groups after the intervention (P = 0.0001). In the peer education group, the mean anxiety score was 5.34 ± 2.52 and decreased to 3.69 ± 2.87 after the intervention (P = 0.0001). In the orientation tour group, the mean anxiety was 5.53 ± 3.49, which and changed to 3.10 ± 2.22 (P = 0.0001). However, the mean anxiety score significantly increased in the control group (5.66 ± 2.94 vs. 6.53 ± 3.43, P = 0.017). Conclusions Both methods of peer education and orientation tour decreased the anxiety levels in patients undergoing coronary artery angiography. Therefore, these approaches should be carried out according to the hospital condition and facilities.